Cysteine-rich angiogenic inducer 61 (CCN1) independently predicts all-cause mortality in patients with dilated cardiomyopathy. (14th October 2021) - Klingenberg, R; Gross, S; Lehnert, K; Wegner, D; Hamm, C.W; Felix, S; Keller, T; Doerr, M
Abstract: Introduction: Cysteine-rich angiogenic inducer 61 (Cyr61, CCN1) is a member of the CCN family of matricellular proteins exerting key functions in inflammation and fibrotic turnover. Recently it has been shown that CCN1 improves risk stratification for all-cause mortality in ACS patients. Purpose: Since both inflammation and fibrosis are key processes involved in the pathogenesis of dilated cardiomyopathy (DCM), we aimed to investigate the prognostic value of CCN1 serum levels for survival in a large cohort of DCM patients. Methods: The cohort compromised patients with a primary diagnosis of DCM, defined as a reduced left ventricular ejection fraction (LVEF <45%) and an increased left ventricular enddiastolic diameter according to the HENRY score (LVEDD according to HENRY >117%) at the time of diagnosis. Exclusion criteria were primary valvular diseases (≥ second degree), acute myocarditis, active infectious diseases, pulmonary diseases, cancer, chronic alcoholism and heart failure of other origins. CCN1 levels were determined in human serum using an enzyme-linked immunosorbent assay (R&D Systems, USA). Multivariable cox regression models for the association between CCN1 and all-cause mortality were adjusted for age, sex, disease duration, LVEF, estimated glomerular filtration rate (eGFR) measured based on the CKD-EPI formula, high-sensitivity C-reactive protein (hs-CRP) and aminoterminal-proB-type natriuretic peptide (NT-proBNP) levels. Results: 306 DCM patients had available biomarker and clinico-demographic data in this single-center cohort (79.3% males) with a mean age of 55.2 years [interquartile range [IQR] 47.9, 64.8]). On average, disease duration was 0.3 years (IQR 0.9, 1.9), LVEF 31% (IQR 25, 37), LVEDD 67.7 mm (IQR 63, 72), and eGFR 91.5 ml/min (IQR 74.1, 102.4). During a median follow-up of 12.5 years (IQR 10.5, 14.1), a total of 114 (37.3%) patients died. Multivariable-adjusted cox regression models revealed an increasing all-cause mortality risk across CCN1 tertiles (p for trend = 0.03), with the highest incidence in the highest tertile (hazard ratio [HR] 1.75; 95%-CI 1.04, 2.94; P=0.034) as compared to the lowest tertile (Figure 1). Conclusion: CCN1 predicts long-term survival in DCM patients independent of NT-pro-BNP and other risk determinants. Further research needs to evaluate whether this novel biomarker also plays a causal role in the pathogenesis of DCM. Funding Acknowledgement: Type of funding sources: Public Institution(s). Main funding source(s): Kerckhoff Foundation